Evaluation of Ceftiofur-Phbv Microparticles in Rats - Constandil-Cordova, L; Vilos-Ortiz, C; Velasquez, L (Dove Medical Press Ltd., 2014)
Despite the high number of antibiotics used for the treatment of infectious disease in animals, the development of slow release formulations presents a significant challenge, particularly in using novel biomaterials with low cost. In this report, we studied the pharmacokinetics, toxicity, and therapeutic activity of ceftiofur-PHBV (ceftiofur-poly(3-hydroxybutyrate-co-3-hydroxyvalerate)) in rats. The pharmacokinetic study demonstrated a sustained release of ceftiofur into the bloodstream, with detectable levels over the minimum inhibitory concentration for at least 17 days after a single intramuscular injection of ceftiofur-PHBV (10 mg/kg weight). In addition, the toxicological evaluation of biochemical, hematological, and coagulation blood parameters at the therapeutic dose demonstrated the safety of ceftiofur-PHBV, with no adverse effects. In addition, ceftiofur-PHBV exhibited a therapeutic effect for a longer time period than the nonencapsulated ceftiofur in rats challenged with Salmonella Typhimurium. The slow release of ceftiofur from the ceftiofur-PHBV, its low toxicity in the blood parameters evaluated, and the efficacy in the rats infected with Salmonella Typhimurium make ceftiofur-PHBV a strong candidate for biotechnological applications in the veterinary industry. © 2014 Vilos et al.